Association Between Diet Type and Owner‐Reported Health Conditions in Dogs in the Dog Aging Project - Alexandra Varela Ortiz; Ingrid Luo; Janice O'Brien; Maryanne Murphy; Angela Witzel Rollins; Matt Kaeberlein; Dog Aging Project Consortium; Audrey Ruple; Kathleen F. Kerr; M. Katherine Tolbert (Journal of Veterinary Internal Medicine)
ABSTRACT Background Alternative dog diets, such as home‐cooked and raw, have grown in popularity. Claims regarding health benefits for these diets have limited supporting evidence. Objectives To evaluate whether feeding home‐cooked, commercial raw, or homemade raw diets is associated with health conditions compared to extruded diets. Animals Twenty‐seven thousand four hundred seventy‐eight dogs. Methods Cross‐sectional, survey‐based study. We analyzed a large cross‐sectional dataset (n = 27 478) of dogs fed homemade cooked (n = 1214), commercial raw (n = 961), homemade raw (n = 329), or extruded (n = 24 974) diets. We investigated associations between diet and 13 owner‐reported health condition categories. Logistic regression was used for the analysis of all health conditions. Results Controlling for sex, age, and body size or breed, a home‐cooked diet was associated with higher odds of gastrointestinal (adjusted odds ratio (aOR): 1.4; 95% confidence interval (CI): 1.2–1.7), renal (aOR: 1.3; CI: 1.1–1.6), and hepatic disease (aOR: 1.6; CI: 1.2–2.0) compared to an extruded diet. A commercial raw diet was associated with higher odds of respiratory disease (aOR 1.7; CI: 1.3–2.3) compared to an extruded diet. Conclusions Analysis of cross‐sectional data can only suggest effects of diet on health and are most useful for hypothesis generation or for testing existing hypotheses.